Long-term success in percutaneous valve commissurotomy – is Wilkins score over 9 a definitive limit?. (3rd October 2022) - Martins De Carvalho, M; Alves Pinto, R; Proenca, T; Calvao, J; Martins Da Costa, C; Amador, A F; Amaral Marques, C; Cabrita, A; Santos, L; Oliveira, C; Pinho, A; Sousa, C; et al.
Abstract: Background: Percutaneous valve commissurotomy (PMC) is an established treatment in patients with significative mitral stenosis (MS). Although rheumatic MS incidence has decreased in the last century, it remains a prevalent pathology worldwide. The Wilkins score (WS) is a reference in echocardiographic assessment of MS; a score ≤8 is considered a predictor of treatment success and score between 9 and 11 is a "grey zone" (WGZ) in which doubts persists regarding PMC success. Purpose: To evaluate the early and long-term results of PMC in patients with rheumatic MS and to compare long-term events between patients with WS ≤8 and patients in WGZ. Methods: We retrospectively analysed all patients between 1991 and 2008 with significative rheumatic MS undergoing PMC. Data were collected at baseline and during long-term follow-up. M ACE was defined as a composite of all-cause mortality, mitral valve re-intervention or cardiovascular hospitalization. Results: In our cohort, 124 patients were included. Most were female (87%), mean age at the time of repair was 46±11 year-old and mean follow-up was 20±6 years. Before the procedure, 81% had WS ≤8 and 19% were in WGZ. Both groups had similar baseline characteristics, namely age at first intervention, NYHA class and follow-up time. All patients had preserved biventricular systolic function, 83% presented PH, mean transvalvular gradient (TVG) and mitral valve area (MVA) were 12.8 mmHg and 1.0 cm 2, respectively. Most of the procedures were successful (91%) and without complications (94%). Mean MVA improvement was similar in both groups [0.9 cm 2 in WS ≤8 and 0.8 cm 2 in WGZ, t(102)=0.173, p=0.863]; there was also no significative difference in TVG and PASP reduction after PMC. During long-term follow-up, re-intervention and mortality occurred in 40% and 23% in WS ≤8 and in 50% and 29% in WGZ, respectively, and none of these differences was statistically significant (p=0.389 and p=0.544, respectively). Concerning time-to-event analysis, approximately 80% of patients kept uneventful and >90% alive after 10 years in both groups and no significant difference in M ACE events and all-cause mortality between WS ≤8 and WGZ was observed (Log Rank, p=0, 419 and p=0.950, respectively). Conclusion: PMC was safe and effective in clinically significant rheumatic MS in both WS ≤8 and WS 9–11, with similar MVA improvement. After 10 years, approximately 80% of patients were MACE-free and >90% alive in both groups. There was no difference in all-cause mortality and in a composite of all-cause death, mitral valve re-intervention or cardiovascular hospitalization concerning WS groups. Funding Acknowledgement: Type of funding sources: None.